Co-occurrence, bioaccumulation, and dietary risk assessment of per- and polyfluoroalkyl substances and heavy metals in rice - Attia, Samir; Hu, Zhiyuan; Qi, Fangjie; Li, Dongling; Coulon, Frederic; Song, Xin (American Chemical Society (ACS), 2026)
The co-occurrence and combined dietary health risks of per- and polyfluoroalkyl substances (PFASs) and heavy metals (HMs) in rice remain poorly understood. This study analyzed 29 PFAS compounds and 4 HMs in rice tissues collected from paddy fields. HFPO-DA was dominant in brown rice (4.84–15.99 ng/g), while PFOA primarily accumulated in leaves and straw. Cd and Cu showed elevated grain concentrations. PFASs exhibited higher bioaccumulation and translocation factors than HMs, especially in aboveground tissues, whereas Cd and As accumulated most in roots. Correlation analyses suggest dual root and foliar uptake contributed to HFPO-DA and Cd grain accumulation. Dietary assessment revealed that HFPO-DA, PFOS, Cd, and Cu in brown rice exceeded safety thresholds across different age groups. Specifically, the cumulative hazard index (HI) reached 10.7 in brown rice for toddlers, twice that of white rice, raising significant health risk concerns. These findings provide critical insights for future food safety monitoring and risk management.
Keywords: PFASs; heavy metals; bioaccumulation; translocation; health risk assessment; 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; Nutrition; Prevention; Endocrine Disruptors; Food Science; 30 Agricultural, veterinary and food sciences; 34 Chemical sciences; 40 Engineering; Humans; Metals, Heavy; Fluorocarbons; Soil Pollutants; Risk Assessment; Food Contamination; Oryza; Dietary Exposure; Bioaccumulation